2018
DOI: 10.1038/s41419-018-0295-5
|View full text |Cite
|
Sign up to set email alerts
|

MYCN drives glutaminolysis in neuroblastoma and confers sensitivity to an ROS augmenting agent

Abstract: Heightened aerobic glycolysis and glutaminolysis are characteristic metabolic phenotypes in cancer cells. Neuroblastoma (NBL), a devastating pediatric cancer, is featured by frequent genomic amplification of MYCN, a member of the Myc oncogene family that is primarily expressed in the early stage of embryonic development and required for neural crest development. Here we report that an enriched glutaminolysis gene signature is associated with MYCN amplification in children with NBL. The partial knockdown of MYC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 57 publications
2
57
1
Order By: Relevance
“…Treatment of NB cells with rapamycin for 24 h has been shown to increase cellular levels of ROS [70], which is consistent with the increases in cellular oxidative stress in MYCN-amplified SK-N-BE(2) cells induced by ISLQ treatment for 24 h, found in our study. It is also worth noting that MYCN amplification has recently been shown to increase ROS, and to confer sensitivity to an ROS-augmenting agent in NB cells [71]. Our present study is consistent with this, as it found that ISLQ had cytotoxic effects at concentrations of 5 μM or greater, on MYCN-IMR-32 and MYCN-amplified SK-N-BE(2) cells.…”
Section: Discussionsupporting
confidence: 91%
“…Treatment of NB cells with rapamycin for 24 h has been shown to increase cellular levels of ROS [70], which is consistent with the increases in cellular oxidative stress in MYCN-amplified SK-N-BE(2) cells induced by ISLQ treatment for 24 h, found in our study. It is also worth noting that MYCN amplification has recently been shown to increase ROS, and to confer sensitivity to an ROS-augmenting agent in NB cells [71]. Our present study is consistent with this, as it found that ISLQ had cytotoxic effects at concentrations of 5 μM or greater, on MYCN-IMR-32 and MYCN-amplified SK-N-BE(2) cells.…”
Section: Discussionsupporting
confidence: 91%
“…However, sensitivity of N-Myc high cells to inhibition of glutamine metabolism could not be rescued by external glutathione supply. Moreover, N-Myc high cells were not significantly more sensitive to the ROS-inducing agent, dimethyl fumarate, which was described to suppress neuroblastoma cell proliferation 20 . Thus, preferential killing of N-Myc high cells in the presence of glutamine metabolism inhibitors and limited glutamine supply cannot be explained by increased consumption of glutathione and increased ROS sensitivity.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, Myc-driven liver tumors rather consume glutamine by a process termed glutaminolysis, which allows for fueling into the tricarboxylic acid cycle (TCA cycle) at the level of α-ketoglutarate by activation of glutaminase, another Myc-target 19 . MYCN-driven glutaminolysis has been recently suggested as a strategy to treat Myc-driven cancers 20 . Still, tumor cell-intrinsic response patterns as a consequence of MYCN activation under varying nutrient conditions largely remain to be identified.…”
mentioning
confidence: 99%
“…However, sensitivity of MYCN high cells to inhibition of glutamine metabolism could not be rescued by external glutathione supply. Moreover, MYCN high cells were not significantly more sensitive to the ROS-inducing agent, dimethyl fumarate, which was described to suppress neuroblastoma cell proliferation 19 . Thus, preferential killing of MYCN high cells in the presence of glutamine metabolism inhibitors and limited glutamine supply cannot be explained by increased consumption of glutathione and increased ROS sensitivity.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, MYC-driven liver tumors rather consume glutamine by a process termed glutaminolysis, which allows for fueling into the TCA cycle at the level of α-ketoglutarate by activation of glutaminase, another MYC-target 18 . MYCN-driven glutaminolysis has been recently suggested as a strategy to treat MYC-driven cancers 19 . Still, tumor cell-intrinsic response patterns as a consequence of MYCN activation under varying nutrient conditions largely remain to be identified.…”
Section: Introductionmentioning
confidence: 99%